Spontaneous spatial order in two-dimensional ferromagnetic spin-orbit coupled uniform spin-1 condensate solitons - Adhikari, S. K. [UNESP] (Elsevier, 2021)
We demonstrate spontaneous spatial order in stripe and super-lattice solitons in a Rashba spin-orbit (SO) coupled spin-1 uniform quasi-two-dimensional (quasi-2D) ferromagnetic Bose-Einstein condensate (BEC). For weak SO coupling, the solitons are of the (−1,0,+1) or (0,+1,+2) type with intrinsic vorticity, where the numbers in the parentheses denote angular momentum in spin components Fz=+1,0,−1, respectively. For intermediate SO coupling, three types of solitons are found: (a) circularly-asymmetric solitons, (b) circularly-symmetric (−1,0,+1)- and (c) (0,+1,+2)-type multi-ring solitons maintaining the above-mentioned vortices in respective components. For large SO coupling, quasi-degenerate stripe and super-lattice solitons are found in addition to the circularly-asymmetric solitons. A super-lattice soliton forms a 2D square lattice structure in the total density as in a super-solid; in component densities it may have either (i) a 1D stripe pattern or (ii) a 2D square lattice structure.
Keywords: Bose-Einstein condensate; Soliton; Spin-1 spinor; Spin-orbit coupling